Analisis Kepuasan Konsumen Umkm Ayam Sambal Geledek di Nusa Indah Kota Bengkulu Menggunakan Metode Customer Satisfaction Index (CSI) Dan Importance Performance Analysis (IPA) - Muhammad Ilham Ramadhan; Taufik Hidayat; Fansor Farere; Pajar Dwi Saputra; Kevin Anugrah; Ririn Harini (Yayasan Darussalam Bengkulu, 2026)
This study aims to analyze consumer satisfaction with UMKM Ayam Sambal Geledek located in Nusa Indah, Bengkulu City. The research applies the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods to measure overall satisfaction levels and identify priority attributes for improvement. Data were collected from 100 respondents using purposive sampling, with respondents selected based on having purchased the product at least twice. The results show that the CSI value reached 79.38%, indicating that consumers are generally satisfied with the product and services provided. Furthermore, the IPA analysis reveals that several attributes, such as brand labeling and product information, fall into the main priority quadrant, meaning they are important but have not performed optimally. Meanwhile, attributes such as price competitiveness, product variation, and service speed are in the “keep up the good work” quadrant. These findings suggest that although overall satisfaction is high, improvements are still needed in specific attributes to enhance consumer loyalty and competitiveness